Posttraumatic Cognitions Differ Between Men and Women after Military Sexual Assault Revictimization in Their Contribution to PTSD Symptoms - Tannahill, Hallie S. (Journal of interpersonal violence, 2023)
Sexual revictimization is heightened among military service members and veterans and is associated with greater posttraumatic stress symptoms (PTSS) and severity. The heightened distress following revictimization may be due to posttraumatic cognitions (PTC), which include negative beliefs about the self and world, and self-blame. Moreover, it is unclear whether men and women experience different levels of PTC. The current study tested PTC (overall and subdomains) as a possible mediator between sexual revictimization and PTSS severity, and gender as a possible moderator of these associations. Revictimization was defined across time periods (military sexual assault [MSA] only vs. premilitary sexual trauma + MSA) and in military rape frequency (0, 1, 2+). Participants were 400 (n = 200 [50%] male) service members/veterans with a history of MSA and completed online, anonymous, self-report questionnaires. PTC mediated the association between revictimization and PTSS severity. A significant interaction of gender suggested that men reported high overall PTC and PTC about the self regardless of revictimization; by contrast, overall PTC and PTC about the self were lower for women in response to MSA only and increased with revictimization. Results also showed men were more sensitive to PTC about self-blame as it pertains to more severe PTSS compared to women. There were no unique gender interactions when assessing revictimization by rape frequency, although PTC (overall, all subdomains) significantly mediated the association between rape frequency and PTSS severity. PTC may be a beneficial target when treating PTSS in men, and may be especially heightened in women who have experienced revictimization.